2015
DOI: 10.1016/j.wjorl.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of p16, cyclin D1, Rb and MIB‐1 levels in skull base chordoma and chondrosarcoma

Abstract: ObjectiveTo investigate the expression of p16, cyclin D1, retinoblastoma tumor suppressor protein (Rb) and MIB-1 in skull base chordoma and chondrosarcoma tissues, and to determine the clinicopathological significance of the above indexes in these diseases.MethodsA total of 100 skull base chordoma, 30 chondrosarcoma, and 20 normal cartilage tissue samples were analyzed by immunohistochemistry. The expression levels of p16, cyclinD1, Rb and MIB-1 proteins were assessed for potential correlation with the clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that factors affecting prognosis include patient's age, tumor size, tumor site, and vascular involvement (5)(6)(7). Meanwhile, some molecular markers such as high expression of Ki-67 and MIB-1 are associated with poor prognosis and high recurrence rate (8)(9)(10). However, the effect of the extent of surgical resection on skull base chordoma prognosis is not clear and needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that factors affecting prognosis include patient's age, tumor size, tumor site, and vascular involvement (5)(6)(7). Meanwhile, some molecular markers such as high expression of Ki-67 and MIB-1 are associated with poor prognosis and high recurrence rate (8)(9)(10). However, the effect of the extent of surgical resection on skull base chordoma prognosis is not clear and needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…The p16 gene can inhibit the progression of a variety of tumors and encode the nucleotide protein (p16 protein) to significantly inhibit the cyclin-dependent kinase 4 (CDK4), thus playing an important role in the progression of various tumors (6). Cyclin D1, as a key cell cycle regulatory protein, can bind to CDK4/6 to form the binary complex and keep cells in S phase, thus promoting cell proliferation (7). Dreyer et al (8) showed that both p16 and cyclin D1 can competitively bind to CDK4, thereby regulating the occurrence and development of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, YBX1 regulates tumor cell proliferation, apoptosis, invasion, migration and chemoresistance through the related pathways . Multiple key molecules that interact with YBX1 have been shown to be overexpressed in chordoma and contribute to chordoma development, such as hypoxia inducible factor 1 alpha subunit (HIF‐1α), a mechanistic target of rapamycin kinase (mTOR) and RB transcriptional corepressor 1 (RB) …”
Section: Introductionmentioning
confidence: 99%
“…10 Multiple key molecules that interact with YBX1 have been shown to be overexpressed in chordoma and contribute to chordoma development, such as hypoxia inducible factor 1 alpha subunit (HIF-1α), a mechanistic target of rapamycin kinase (mTOR) and RB transcriptional corepressor 1 (RB). 6,[11][12][13][14] Receptor tyrosine kinases (RTK) have been proved to participate in the tumorigenesis and development of chordoma. The epidermal growth factor receptor (EGFR) is the most significantly activated RTK in chordoma.…”
mentioning
confidence: 99%